Study of morphoagronomic indicators of Cenchrus purpureus clones for biomass production - Herrera, R.; Fortes, dayleni; García, M.; Cruz, Ana M. (Cuban Journal of Agricultural Science, 2019)
Using a randomized block design with four replications, clones of Cenchrus purpureus (CT-6, CT-9, CT-13, CT-15, CT-24 and CT-28) obtained by in vitro tissue culture were evaluated and compared with their progenitor (CT-115) in typical red Ferralitic soil, for two years without irrigation and fertilization. In both evaluation years during the seasonal periods the height differed (P<0.001) between the clones and the CT-28 surpassed the CT-115 was highlighted. There were differences (P <0.001) in the percent of DM and their values varied in narrow range (17-23 % and 19-21 % in the dry and rainy season, respectively). With the exception of CT-24, the rest of clones showed leaves contents higher than 50 % and differed among them, but the highest value (64.88 %, P <0.001) was showed by CT-28 during the rainy season. The leaves length varied (P <0.0001) between clones and CT-9 was highlighted in both years (73.73 and 84.23 cm for the dry and rainy season, respectively for the first year and 68.6 and 76.7 cm for similar stages of the second year). Similar response pattern was obtained in the leaf width. The leaf area also differed between clones and the highest values were recorded in the rainy season of both years. There were significant differences between the clones in the seasonal and annual DM yield and the clones CT-9, CT-15, CT-24 and CT-28 were highlighted. There were also significant differences in the population of the clones at the beginning and end of the experiment, but when comparing these two stages there were not variation and the values ranged between 5.43 and 9.49 bunches/5m. In general terms, the studied indicators varied when comparing the studied years. There is a group of clones with favorable characteristics for forage production, where CT-9 and CT-28 were highlighted. Future studies using strategic fertilization and irrigation of promising clones are suggested. Key words: height, yield, leaves, population, leaf area